Epiphytic ferns and lycophytes of Veracruz, Mexico: species richness and distribution - Mendoza-Ruiz, Aniceto; Ceja-Romero, Jacqueline; Pérez-García, Blanca (Instituto de Ecología, A.C., 2016)
Based on the review of herbarium material and specialized literature, as well as recollection of botanical specimens, we obtained information about the species richness, municipal distribution, vegetation type and altitudinal range of epiphytic ferns and lycophytes that occur in the state of Veracruz, Mexico. We recorded 11 families, 33 genera and 173 species with at least one herbarium voucher, and 23 cited in the literature. The families with highest species number were Polypodiaceae, Dryopteridaceae and Hymenophyllaceae, whereas the genera with most taxa were Polypodium, Asplenium, Trichomanes and Elaphoglossum. Most plants are distributed in cloud forest, tropical evergreen forest and oak forest, in an altitudinal range from 751 to 1750 m.